Integrating English Instruction with Contemporary Islamic Values: A Literature Review - Krisna Dwi Alifhia Rezky; Zaitun Qamariah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The integration of English language teaching with contemporary Islamic educational values is an innovative approach that combines language mastery with character development based on Islamic principles. This approach aims to address dual needs: fostering global competencies while preserving cultural and religious identity. Integrating values such as honesty, responsibility, respect, and tolerance into the English curriculum enriches the learning experience and promotes character building among students. Teachers play a vital role as facilitators, utilizing creative and culturally relevant materials, such as Islamic texts, Qur'anic stories, and historical narratives, to create a meaningful learning environment. This approach not only enhances language skills but also instills ethical and spiritual dimensions in education. Despite challenges such as limited teacher training and the availability of suitable teaching materials, the integration of Islamic values into English language teaching offers a holistic framework for shaping individuals who are both globally competent and morally grounded. This study emphasizes the importance of aligning educational practices with Islamic principles to prepare students for a connected modern world while preserving their religious and cultural heritage.